PENGARUH SARANA DAN PRASARANA TERHADAP PRESTASI BELAJAR PESERTA DIDIK DI SD MUHAMMADIYAH 07 TERPADU PEKANBARU - Agustina, Eria; Nurul Hidayah; Putri Lestari; Tatia Alvina; Dea Mustika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research examines how school facilities or infrastructure affect student academic performance. This research focuses on the impact of infrastructure on schools. The aim of this research is to find out how elementary school infrastructure affects learning activities and student learning outcomes. This research uses an associative method, which is a form of investigating cause and effect relationships. Fourth grade students at SD Muhammadiyah 07 Integrated Pekanbaru participated in this research. Data was collected using direct contact techniques and tools such as questionnaires and interview guides. Based on the regression equation ζ = 4.175 + 0.504 t tabel = 1.985, there is a positive influence of 4.3% between the school facilities and infrastructure variable (X) on student learning achievement (Y), and Ho is rejected. Therefore, at a significance level of 5% it can be said that Ha is accepted and Ho is rejected because t hitung is greater than t tabel. Thus, the integrated school facilities and infrastructure of SD Muhammadiyah 07 Pekanbaru have a good and big influence on student learning success.